Early closure of temporary ileostomy—the EASY trial: protocol for a randomised controlled trial - Eva Angenete; Eva Haglind; Anne Kjaergaard Danielsen; Adiela Correa-Marinez; Stefan Skullmann (BMJ Open)
Objective The objective is to evaluate efficiency based on data on morbidity and mortality, health-related quality of life and healthcare-related costs after early reversal of temporary ileostomy after rectal resection for cancer compared with the standard procedure (late reversal).Background Reversal of a temporary ileostomy is generally associated with a low morbidity and mortality. However, ostomy reversal may cause complications requiring reoperation with subsequent major complications, in ranges from 0% to 7–9% and minor complications varying from 4–5% to 30%. Based on studies exploring and describing the time of closure in previous studies which are mostly of low quality, a recent review concluded that closing a temporary stoma within 2 weeks did not seem to be associated with an increase in morbidity and mortality.Design and methods Early closure of temporary ileostomy (EASY), a randomised controlled trial, is a prospective randomised controlled multicentre study which is performed within the framework of the Scandinavian Surgical Outcomes Research Group (http://www.ssorg.net/) and plans to include 200 patients from Danish and Swedish hospitals. The primary end-point of the study is the frequency of complications 0–12 months after surgery (the stoma creation operation). The secondary end-points of the study are (1) comparison of the total costs of the two groups at 6 and 12 months after surgery (stoma creation); (2) comparison of health-related quality of life in the two groups evaluated with the 36-item short-form and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-CR29/CR30 at 3, 6 and 12 months after surgery (stoma creation); and (3) comparison of disease-specific quality of life in the two groups at 3, 6 and 12 months after surgery (stoma creation).Discussion The aim of the EASY trial is to evaluate the efficiency of early reversal of temporary ileostomy after surgery for rectal cancer versus late reversal. The EASY trial is expected to have a huge impact on patient safety as well as an improvement in patient-reported outcome.Clinical trials identifier NCT01287637.